Use of MRI for Lobar Classification of Benign Prostatic Hyperplasia: Potential Phenotypic Biomarkers for Research on Treatment Strategies - Wasserman, Neil F. (AJR Am J Roentgenol, 2015)
PURPOSE: We present an MRI classification of benign prostatic hyperplasia (BPH) for use as a phenotype biomarker in the study of proposed therapeutic interventions. METHODS: T2 weighted magnetic resonance images were obtained at 3 Tesla in patients with suspicion of adenocarcinoma. Previous BPH classifications are reviewed, and implications for inclusion of lobar classification in therapeutic research for BPH are discussed. SUMMARY: Six patterns of BPH distribution were identified. Illustrations are shown for each classification type.